The relationship between learning motivation and learning outcomes of grade V students of SD Negeri Kupang 03 - Dina Chrisnawati; Ridha Sarwono; Atrianing Yessi Wijayanti (Cendikia : Media Jurnal Ilmiah Pendidikan, 2026)
This study investigated the relationship between learning motivation and learning outcomes among fifth-grade students at SD Negeri Kupang 03, where low classroom participation, limited enthusiasm, and many scores below the Minimum Completeness Criteria (KKM) were identified as key educational issues. The study applied a quantitative approach with a correlational design. From a population of 102 students, 28 fifth-grade students were selected through purposive sampling. Data collection was carried out using a closed-ended questionnaire to assess learning motivation and documentation of Mid-Semester Test scores to measure learning outcomes. The data were analyzed using Pearson’s Product Moment correlation test. The results revealed a positive and statistically significant relationship between learning motivation and learning outcomes (rxy = 0.642), which was higher than the rtable value of 0.374 at the 5% significance level. The correlation was categorized as strong, indicating that students with higher learning motivation tend to achieve better academic outcomes. These findings highlight the importance of fostering motivation to improve students’ academic performance.